Correlation between risk factors and low back pain in physiotherapy students of a public higher education institution (Research, Society and Development, 2022)
Low back pain is multifactorial and can arise from dysfunction of the spinal muscles, which can trigger muscle fatigue due to excessive overloads imposed on the structures of the lumbar spine: ligaments, capsules and intervertebral discs, causing the plastic alteration of these elements sensitive to distension. Furthermore, when recruiting a muscle group too much, or leaving them immobile for long periods or even by pathological and inflammatory processes in the tissues. The aim of this study was to identify factors associated with low back pain in students from a public Higher Education Institution. This is a cross-sectional, descriptive field research with a quantitative approach to data. As for the results, 32 physical therapy students participated in this study. It was possible to observe that 90.6% of the sample reported low back pain. Correlation between the prevalence of back pain and sitting for a long period, the Chi-Square test reveals that there is not enough evidence to conclude that the variables are associated, however, it is known that sitting for a long period has the possibility of cause a certain deficit in the muscles and joints, as well as in flexibility and mobility, in addition to fatigue in the posterior muscles of the spine. It is proposed to carry out new studies using the same or other methods to confirm or oppose the results found, as well as to expand and deepen such content.